The varying roles of governance mechanisms on ex-post transaction costs and relationship commitment in buyer-supplier relationships - Shahzad, Khuram; Ali, Tahir; Takala, Josu; Helo, Petri; Zaefarianc, Ghasem (Elsevier, 2018)
Inter-firm relationship governance is becoming increasingly fragmented and complex in industrial marketing and management. There is a need to develop an integrative framework, which describes the nature of the relationship (complementary or substitutes) between economic and sociological governance mechanisms, and their relative effectiveness in explaining ex-post transaction costs and relationship commitment. Building on transaction cost economics (TCE) and social exchange theory (SET), we investigate the varying roles of economic (i.e., contract completeness and symmetric dependence) and sociological (i.e., trust and communication) governance mechanisms. The deductive-nomological framework is tested by employing a nonparametric technique (i.e., partial least squares - PLS) to structural equation modeling (SEM) and semi-partial correlation. The analysis of data from 170 buyer-supplier relationships established by Finnish SMEs indicates that sociological mechanisms function as substitutes with contractual governance and complementary with symmetric dependence in relation to ex-post transaction costs and relationship commitment. Further, economic governance mechanisms have a more effective role in minimizing ex-post transaction costs, whereas sociological governance mechanisms are more powerful in enhancing relationship commitment.
Keywords: relationship governance mechanisms; ex-post transaction costs; relationship commitment; buyer-supplier relationships; structural equation modeling; fi=Tuotantotalous|en=Industrial Management|